Building Trust in the Midst of Crisis: Brand Communication Strategies in the Digital Age - ., Novitasari; Doho, Yohannes Don Bosco (Journal of Ecohumanism, 2024)
The digital age is full of challenges, crises that can occur so quickly and spread more widely than ever before. In the midst of a situation like this, a brand's ability to rebuild trust becomes very important. This research aims to analyze effective crisis communication strategies in building and maintaining public trust through a qualitative approach. The theory used is situational crisis communication theory (SCT) to explore how a brand's communication response can influence public perception and consumer loyalty during a crisis. By conducting in-depth interviews and case study analysis, the research explored how transparency, speed and empathy played a key role in shaping the brand's image amid the crisis. The research confirms that brands adopt a proactive approach to crisis communications, by establishing clear protocols for rapid response, building an authentic digital presence, and engaging brand leaders directly to show genuine commitment. With an approach that emphasizes humanistic communication, crises can be an opportunity to demonstrate core brand values and increase loyalty. In the midst of a crisis, brand communication actors are expected to uphold proactivity, speed in responding, and the importance of authenticity in communication so that trust in the communicated brand is maintained.